2023
DOI: 10.1039/d2mh01382g
|View full text |Cite
|
Sign up to set email alerts
|

From optical pumping to electrical pumping: the threshold overestimation in metal halide perovskites

Abstract: The threshold carrier density, conventionally evaluated from optical pumping, is a key reference parameter towards electrically pumped lasers, with the widely acknowledged assumption that optically excited charge carriers relax to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…10,11 Many-body effects and strong Coulomb interactions occurring after photoexcitation lead to intrinsic bandgap shrinking. 12,13 Although this phenomenon is commonly observed in various semiconductor materials, its overall behaviour is dictated by the competition among several different effects, and the exact origin and mechanism remain unclear. Transient spectroscopic characteristics induced by femtosecond (fs) pump and probe laser In this study, we have demonstrated the significant role of phonons in the photo-induced transient bandgap renormalization (BGR) of MAPbBr 3 perovskite single crystals, in addition to the contribution from photogenerated hot carriers.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Many-body effects and strong Coulomb interactions occurring after photoexcitation lead to intrinsic bandgap shrinking. 12,13 Although this phenomenon is commonly observed in various semiconductor materials, its overall behaviour is dictated by the competition among several different effects, and the exact origin and mechanism remain unclear. Transient spectroscopic characteristics induced by femtosecond (fs) pump and probe laser In this study, we have demonstrated the significant role of phonons in the photo-induced transient bandgap renormalization (BGR) of MAPbBr 3 perovskite single crystals, in addition to the contribution from photogenerated hot carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a weak positive signal promptly appears at subpicosecond time scales on the lower-energy side of the optical gap, which is attributed to band gap renormalization (BGR). The origin of these transient signals in the visible region has been extensively discussed previously. ,, It is worth noting that the negative peak at 2.35 eV undergoes a red shift at early times, which can be attributed to the interplay between the red shift due to BGR and the blue shift resulting from the Burstein–Moss effect (see Figures S4 and S5 for the normalized spectral traces and time traces, Supporting Information). However, it has been reported that under band edge excitation, inorganic perovskite nanocrystals induce a transient blue shift attributed to polaron formation on the 300 fs time scale. , …”
Section: Resultsmentioning
confidence: 99%
“…We note that in a recent paper, the faster carrier cooling processes under longer wavelength excitation have been considered as another cause of the lower threshold. [ 32 ] We also measured the lasing behaviors under CW pumping of different lasting times. As can be seen in Figure S12 (Supporting Information), with temperature increasing (caused by increasing the lasting time), the intensity ratio of stimulated emission to spontaneous emission gradually decreases and the lasing threshold gradually increases, confirming that heat‐induced optical loss is the dominant cause of the lasing suppression.…”
Section: Resultsmentioning
confidence: 99%